2018
DOI: 10.1111/wej.12338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of run‐of‐the‐river hydropower plants on the surface water quality in the Solakli stream watershed, Northeastern Turkey

Abstract: In recent years, Turkey has turned its attention to alternative energy sources rather than fossil fuels. The Eastern Black Sea Region of Turkey has steep mountains with hilly topography and has large potential in terms of energy production with run‐of‐the‐river hydropower plants (RHPPs). In this study, the effects of two RHPPs on some water quality parameters were examined in the Solaklı stream watershed. This research was conducted over the course of 12 months (January–December 2014). In total, 12 sampling po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
2
5
1
Order By: Relevance
“…Water temperature and dissolved oxygen are variables inversely related (Lewis 1987; Khani and Rajaee 2017; Koralay et al 2018); nevertheless, in this study, a direct relationship was observed, these variations might be explained more by biological effects (photosynthesis-respiration) than by physical aspects (Cervantes-Martínez and Gutiérrez-Aguirre 2015). pH values were closer to the neutrality, probably due to the limestone buffer, according to Razo et al (2004) and Grochowska (2020).…”
Section: Resultscontrasting
confidence: 46%
“…Water temperature and dissolved oxygen are variables inversely related (Lewis 1987; Khani and Rajaee 2017; Koralay et al 2018); nevertheless, in this study, a direct relationship was observed, these variations might be explained more by biological effects (photosynthesis-respiration) than by physical aspects (Cervantes-Martínez and Gutiérrez-Aguirre 2015). pH values were closer to the neutrality, probably due to the limestone buffer, according to Razo et al (2004) and Grochowska (2020).…”
Section: Resultscontrasting
confidence: 46%
“…It was recorded between 5.70 and 6.70 mg.L -1 . This factor has strong negative association with temperature (Koralay et al 2018), whereas the decrease of DO will result in obstruction of algae diversity and biomass (Haas et al 2014). However, this study suggested positive correlation from both factors instead.…”
Section: Environmental Factors Measurement Resultsmentioning
confidence: 99%
“…The lowest concentration were found in April. Oxygen concentration in waters are strongly influenced by temperature (Koralay et al, 2018). The decrease in DO will affect algae diversity and biomass (Haas et al, 2014).…”
Section: Resultsmentioning
confidence: 99%